Factors associated with seropositivity of Hepatitis B & C: A case control study at Azad Jammu and Kashmir - Muhammad Abdul Quddus; Arslan Shahzad; Rukhsana Munawar; Rizwan Saeed Kiani; Humayun Mumtaz; Rabia Tahir (Journal of Rawalpindi Medical College)
OBJECTIVE: To determine the factors associated with seropositivity of hepatitis B and C at Azad Jammu and Kashmir